Exploring the anti-aging potential of phytoestrogens: focus on molecular mechanisms and menopausal symptom modulation - Li, Yuchen; Huang, Feng; Qian, Xin; Liu, Chengdong; Yao, Yi; Wang, Zhangyu; Zhu, Xiaoyi; Guo, Qi (Frontiers in Nutrition, 2025)
The decline in estrogen levels among menopausal women can trigger multisystem dysfunction, significantly increasing the risk of osteoporosis, cardiovascular disease, cognitive impairment, and genitourinary syndrome (GSM). As plant-derived weak estrogen analogs, phytoestrogens demonstrate menopause-related protective potential in preclinical studies by selectively activating ERα, ERβ, and GPER receptor targets to modulate downstream signaling pathways. Current clinical trials indicate their value as an alternative strategy to menopausal hormone therapy (MHT, previously referred to as HRT) for managing menopause-related disorders. Although heterogeneity exists across study outcomes, specific formulations have shown clear efficacy. Future well-designed, large-scale studies are warranted to validate their clinical translational potential.